2013
DOI: 10.1097/sla.0b013e31828ee1da
|View full text |Cite
|
Sign up to set email alerts
|

Low Degree of Formal Education and Musical Experience Predict Degree of Music-Induced Stress Reduction in Relatives and Friends of Patients

Abstract: Music is an effective and inexpensive means of reducing anxiety in friends and family of patients, who are underresearched in medicine. Moreover, low educational attainment and tendency to respond positively to music in a group setting can predict the effectiveness of music-induced relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Patients with comorbidities such as asthma may profit from this relaxation modality by learning about their body’s response to different input while also gaining the control to potentially halt exacerbations of illness. Other mind-body interventions shown to decrease stress include hypnosis, guided imagery, music therapy, and progressive muscle relaxation [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Treatment Of Toxic Stressmentioning
confidence: 99%
“…Patients with comorbidities such as asthma may profit from this relaxation modality by learning about their body’s response to different input while also gaining the control to potentially halt exacerbations of illness. Other mind-body interventions shown to decrease stress include hypnosis, guided imagery, music therapy, and progressive muscle relaxation [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Treatment Of Toxic Stressmentioning
confidence: 99%
“…Music therapy can be extended as an anxiolytic to patients' family members, especially those who spend long periods of time in a waiting room. 9,13,14 A study published in the Annals of Surgery of 346 relatives and friends of patients cared for in the emergency department demonstrated that friends and family experienced less anxiety when classical music was played in the waiting room than when it was not. 14 When working with surgical patients and their families, Humphries includes the family in the patient's preoperative therapy and continues to offer musical relaxation techniques to the family while the patient undergoes the procedure to alleviate their anxiety through that process as well.…”
Section: Benefits For Family Membersmentioning
confidence: 99%
“…Under the influence of music, students can not only feel the beauty, but can also relieve stress, cultivate emotions and improve personality (Li, Huang, Lai et al, 2013). Using music to treat students' psychological problems can guide and alleviate their different psychological problems in a targeted manner (Tilt, Werner, Brown et al, 2013), and further increase the theoretical value of music psychology research (Jansen, Dittrick, Narvaez et al, 2006;Critchlow, Herrington, & Gunton, 2012;Árnason, Briem, & Árnason, 2018).…”
Section: Introductionmentioning
confidence: 99%